2019
DOI: 10.1016/j.jedc.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Firing costs, misallocation, and aggregate productivity

Abstract: For helpful comments we thank participants at the Macroeconomics and Business CYCLE Conference in Santa Barbara and Universidade de Vigo. All remaining errors are our own. Restuccia gratefully acknowledges the financial support from the Canada Research Chairs program and the Social Sciences and Humanities Research Council of Canada. Mendes Tavares gratefully acknowledges the financial support of DIFD. Da Rocha gratefully acknowledges the financial support of Xunta de Galicia (ref. GRC2015/014). The views expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Hsieh and Klenow (2009) show that the resulting misallocation accounts for a significant fraction of the differences in aggregate productivity between the US, China and India and Bartelsman et al (2013) confirm this finding using micro data from OECD countries. 7 Boedo and Mukoyama (2012) and Da-Rocha et al (2019) have shown firing costs hinder job reallocation and reduce allocative efficiency and aggregate productivity. The additional effect of barriers to reallocation when productivity is endogenous is also the focus of Gabler and Poschke (2013), Da-Rocha et al (2019), and Bento and Restuccia (2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Hsieh and Klenow (2009) show that the resulting misallocation accounts for a significant fraction of the differences in aggregate productivity between the US, China and India and Bartelsman et al (2013) confirm this finding using micro data from OECD countries. 7 Boedo and Mukoyama (2012) and Da-Rocha et al (2019) have shown firing costs hinder job reallocation and reduce allocative efficiency and aggregate productivity. The additional effect of barriers to reallocation when productivity is endogenous is also the focus of Gabler and Poschke (2013), Da-Rocha et al (2019), and Bento and Restuccia (2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Hsieh and Klenow (2009) show that the resulting misallocation accounts for a significant fraction of the differences in aggregate productivity between the US, China and India and Bartelsman et al (2013) confirm this finding using micro data from OECD countries. 7 Boedo and Mukoyama (2012) and Da-Rocha et al (2019) have shown firing costs hinder job reallocation and reduce allocative efficiency and aggregate productivity.…”
Section: Related Literaturementioning
confidence: 99%
“…Hsieh and Klenow (2009) show that the resulting misallocation accounts for a significant fraction of the differences in aggregate productivity between the US, China and India and Bartelsman et al (2013) confirm this finding using micro data from OECD countries. 7 Boedo and Mukoyama (2012) and Da-Rocha et al (2019) have shown firing costs hinder job reallocation and reduce allocative efficiency and aggregate productivity. The additional effect of barriers to reallocation when productivity is endogenous is also the focus of Gabler and Poschke (2013), Da-Rocha et al (2019), and Bento and Restuccia (2017).…”
Section: Related Literaturementioning
confidence: 99%
“…7 Boedo and Mukoyama (2012) and Da-Rocha et al (2019) have shown firing costs hinder job reallocation and reduce allocative efficiency and aggregate productivity. The additional effect of barriers to reallocation when productivity is endogenous is also the focus of Gabler and Poschke (2013), Da-Rocha et al (2019), and Bento and Restuccia (2017). Samaniego (2006) highlights the effects of firing costs in a model with productivity growth.…”
Section: Related Literaturementioning
confidence: 99%